The estimation of GFR and ERPF using adaptive edge-based active contour for the segmentation of structures in dynamic renal scintigraphy - Suapang, Piyamas; Dejhan, Kobchai; Yimman, Surapun (My University, 2015)
Dynamic renal scintigraphy is usually applied for the estimation of GFR and ERPF. The clearance of 98mTc-DTPA and 99mTc-MAGS were the relatively index of GFR and ERPF in the clinical evaluation of patients with acute and chronic renal failure using camera-based methods. In camera-based methods it is necessary to manually delineate ROIs for 99Tc-DTPA and 99m Tc-MAG3 calculation. The requirement may reduce the convenience and reliability of estimating GFR and ERPF from dynamic renal scintigraphy. This paper proposes the estimation of GFR and ERPF using adaptive edge-based active contour for the segmentation of structures in dynamic renal scintigraphy. The salient feature of proposed method is based on combining three other external force. First, the adaptive elastic parameter has been developed to automatically adjust the rigidity of the snake during its evolution towards an image contour. Second, the adaptive balloon force has been implemented to increase the GVF snake's captured range and convergence speed. Finally, a dynamic GVF force is introduced to provide an efficient evolution stop mechanism. Preliminary segmentation results demonstrate the potential of proposed method and are visually judged to be acceptable for clinical use in comparison with the original GVF snake method and manual segmentation by experts. Furthermore, the mean of estimating GFR and ERPF with the proposed method are successfully predicted and do not differ from APEX-XPERT program at the 5% level of significance.
Keywords: Dynamic renal scintigraphy; Effective renal plasma flow; Glomerular filtration rate; Region of interest